Effect Of Strategic Plan Implementation On Organizational Performance Of Energy Companies In Somalia - ELMI, HASSAN MOHAMUD; GICHINGA, DR. LUCY GICHINGA (IJRDO - Journal of Applied Management Science, 2018)
The main purpose of this study is to investigate the effect of strategic plan implementation onorganizational performance: a case study of Banaadir Electric Company (BECO).The specificobjectives are to analyze the effects of strategic leadership, structures, strategic resource allocationand strategic policies on organizational performance and to measure the combined contribution offour factors (strategic leadership, structure, strategic policies and strategic resources allocation) onorganizational performance. A descriptive research design will be adopted for this study. Thedependent variable of the study is organizational performance while the independent variables ofthe study were Leadership, structure, policies factors and resource allocation effect oforganizational performance. Most companies struggle with implementation of strategic plans andtherefore fail in performance enhancement and it appears that BECO has had serious problem inimplementing the strategic plan and it is not yet understood how the key components of strategicimplementation including leadership, functional policies, organization structure and resourcesallocation are responsible the performance of the company. This study Sought to establish theeffect of strategic plan implementation on organizational performance in electric companies byanswering the following research question; how strategic plan implementation affects the electriccompanies in Mogadishu? The population consists of the Banaadir Electric Company (BECO)Employees: and target populations were the Top Managers, Middle Managers and first lineManagers. 79 of the Banaadir Electric Company (BECO) managers were used as the sample sizerepresenting the total population. Proportionate stratified random sampling technique will be usedfor this study. The primary data collection tool was used administered questionnaires. A pilot testwas conducted with a few respondents before the questionnaire will be reviewed and then wasdistributed to the selected sample. The data collected in this study was analyzed using descriptivestatistics through SPSS version 22 for windows to provide simple summaries in form of tables,figures and explore relationships between responses to different questions. The results reveal thatstrategic Leadership, structure, strategic policies and strategic resource allocation have significantand positive effects on organizational performance of energy companies in Mogadishu-Somalia.The study recommended that managers of energy companies in Mogadishu -Somalia shouldnurture and develop strategic Leadership, structure, strategic policies and strategic resourceallocation. The areas for further research include a comparative study between a public enterpriseand a private enterprise to find out best practices that can be incorporated in the other sector.